Readiness of Indonesian TVET Teachers in Receiving GIS Technology Using TAM 2 - Bakri, Arya; Sugiarti, Yatti; Wahyudin, Didin (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
Since the enactment of curriculum changes in 2013, several factors have emerged that often become obstacles in geographic and geospatial technical vocational high schools in Indonesia, one of which is minimal acceptance of Geography Information System (GIS) technology. This teacher survey research is to explore the determinant factors that influence the acceptance of GIS technology, through identifying what obstacles are found when the acceptance of GIS technology is integrated in classroom learning. Using survey data from 94 teachers from 34 geographic and geospatial technical vocational schools, question assumptions were formulated using the technology acceptance model (TAM 2), with key determinants of Perceived Usefulness (PU) and User Intention (UI). The lack of knowledge, skills and experience of teachers following GIS training, has caused teachers to be slow in accepting GIS technology. These pressures prevent teachers from reflecting on their teaching, and ultimately result in substitution of teachers intellectual creativity with compliance culture and contribute to the tendency of teachers to prioritize learning experiences that they believe can be directly applied to their own classroom situations. It is clear that the benefits of implementing a classroom will not come alone if the teacher is not ready and trained for the use of GIS technology.